A general Beerkan Estimation of Soil Transfer parameters method predicting hydraulic parameters of any unimodal water retention and hydraulic conductivity curves: Application to the Kosugi soil hydraulic model without using particle size distribution data. (July 2019) - Fernández-Gálvez, J.; Pollacco, J.A.P.; Lassabatere, L.; Angulo-Jaramillo, R.; Carrick, S.
Highlights: A general BEST method is presented for estimating soil hydraulic parameters without the need for particle-size distribution data. Estimation of soil hydraulic parameters can be performed directly by using the quasi-exact implicit formulation ofHaverkamp et al. (1994) . Kosugi and van Genuchten soil hydraulic parameters are satisfactorily retrieved with the methodology. Abstract: Soil hydraulic characterization is crucial to describe the retention and transport of water in soil, but current methodologies limit its spatial applicability. This paper presents a cost-effective general Beerkan Estimation of Soil Transfer parameters (BEST) methodology using single ring infiltration experiments to derive soil hydraulic parameters for any unimodal water retention and hydraulic conductivity functions. The proposed method relies on the BEST approach. The novelty lies in the use of Kosugi hydraulic parameters without need for textural information. In addition, the method uses a quasi-exact formulation that is valid for all times, which avoids the use of approximate expansions and related inaccuracy. The new BEST methods were tested against numerically generated data for several contrasting synthetic soils, and the results show that these methods provide consistent hydraulic functions close to the target functions. The new BEST method is accurate and can use any water retention and hydraulic conductivity functions.